КОНТРОЛЬ ЗА ДІЯЛЬНІСТЮ ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДІВ УКРАЇНИ - Букін, Микола Петрович (SUPREMANCE OF LAW, 2019)
The article deals with the issues of control over the activity of higher education institutions of Ukraine, as well as its main features. Through the analysis of scientific views, the author defines the concepts of “control” and “activity of educational institutions”. It is established that, given the specific status of higher education institutions in Ukraine, exercising control over them and their activities has its own peculiar features. Suggestions are made regarding the improvement of some supervision and control procedures, in particular, the modern administrative and legal support of the professional activity of employees of the controlling bodies. It was also proposed to amend the profile legislation in order to improve the quality level of effective activity of the intra-system units, which exercise constant control over higher educational establishments of Ukraine.